The Existence Local Wisdom of Rice Farming in North Lintau Buo District, Tanah Datar Regency, West Sumatra Province - Cepriadi; Adlin, Fortuna; Arifudin, Arifudin (Indonesian Journal of Social Responsibility Review (IJSRR), 2022)
This research aims to know the existence local wisdom of rice farming in North Lintau Buo Subdistrict, Tanah Datar District, West Sumatra Province. Descriptive qualitative analysis was used with an ethnographic approach, to investigate a culture with in depth interviews and participatory observation. The informants are rice farmers who spread across the five villages of North Lintau Buo Subdistrict. The resultsshowed that rice farmers in Lintau Buo Utara Subdistrict still practice local wisdom, there are 20 total local wisdoms with 13 local wisdoms that are still being implemented are: alek banda/alek tapai, goro talia banda, paraku, pengisian ikan, dipongok, pantangan memilih benih, tapak semaian, penancapan tanaman sicerek, larangan manabang batang kayu, larangan manyabik rumpuik, basiang padi, tawa nan ampek dan manyabik. However there are 7 local wisdoms that are no longer implemented.